Recessive mutations in NDUFA2 cause mitochondrial leukoencephalopathy. Issue 2 (21st December 2017) - Perrier, S.; Gauquelin, L.; Tétreault, M.; Tran, L.T.; Webb, N.; Srour, M.; Mitchell, J.J.; Brunel‐Guitton, C.; Majewski, J.; Long, V.; Keller, S.; Gambello, M.J.; et al.
Abstract : Deficiencies of mitochondrial respiratory chain complex I frequently result in leukoencephalopathy in young patients, and different mutations in the genes encoding its subunits are still being uncovered. We report 2 patients with cystic leukoencephalopathy and complex I deficiency with recessive mutations in NDUFA2, an accessory subunit of complex I. The first patient was initially diagnosed with a primary systemic carnitine deficiency associated with a homozygous variant in SLC22A5, but also exhibited developmental regression and cystic leukoencephalopathy, and an additional diagnosis of complex I deficiency was suspected. Biochemical analysis confirmed a complex I deficiency, and whole‐exome sequencing revealed a homozygous mutation in NDUFA2 (c.134A>C, p.Lys45Thr). Review of a biorepository of patients with unsolved genetic leukoencephalopathies who underwent whole‐exome or genome sequencing allowed us to identify a second patient with compound heterozygous mutations in NDUFA2 (c.134A>C, p.Lys45Thr; c.225del, p.Asn76Metfs*4). Only 1 other patient with mutations in NDUFA2 and a different phenotype (Leigh syndrome) has previously been reported. This is the first report of cystic leukoencephalopathy caused by mutations in NDUFA2 . Abstract :